Third-party Services as a Privacy Threat on University Websites - Heino Timi; Rauti Sampsa; Carlsson Robin; Leppänen Ville (United States, 2025)
As the shift towards digitalization accelerates, and people increasingly rely on online services for everyday tasks, the significance of online privacy concerns keeps rising. This is also true for universities, as they continue transitioning their services and information online. In the current study, we present a technical analysis of the prevalence of third-party analytics on university websites in the EU area. We analyzed the websites of 95 universities from 19 different EU countries. The third-party analytics services employed by the studied websites were identified. The study reveals that the websites of most universities contain concerningly high numbers of analytics. These findings highlight the need to carefully choose and justify the used analytics services, and to assess the personal data websites deliver to third parties. Addressing online privacy concerns is particularly crucial for universities, as they can be considered as institutions dedicated to serving the common good.
CompSysTech '23: Proceedings of the 24th International Conference on Computer Systems and Technologies